Improving The Quality of Learning Through Virtual Laboratory Work Use as Element - Z.R. Mamadaliyeva (Genius Publishing Group, 2022)
The main objectives of laboratory classes are experimental verification of theoretical knowledge; the formation of practical skills and abilities when working with real physical objects and equipment; consolidate the skills of experimental research and processing of the results. To date, the preference is given to the use of traditional forms of laboratory practice using desktop laboratory work in higher education institutions, since they are usually simple and straightforward. The main feature of technical education is the organization and conduct of laboratory practice using real research equipment. Training of specialists of various profiles is impossible without organizing and conducting laboratory classes in basic (basic) subjects of vocational training. The importance of this type of education is confirmed by the current state educational standards
Keywords: laboratory classes; educational standards; skills of experimental